2023
DOI: 10.1002/adma.202303635
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Perovskite Film from Laser Recrystallization in Magnetic Field

Abstract: The orientation of crystals on the substrate and the presence of defects are critical factors in electro‐optic performance. However, technical approaches to guide the orientational crystallization of electro‐optical thin films remains challenging. This article reports on a novel physical method called magnetic field assisted pulse laser annealing (MAPLA) for controlling the orientation of perovskite crystals on substrates. By inducing laser recrystallization of perovskite crystals under a magnetic field and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…While the SPO PCEs for both types of devices were similar, the integrated J sc of ordered-perovskite devices was slightly higher, reinforcing the positive impact of crystal orientation (Figure i,j). Currently, there is a widespread discussion on improving the performance of perovskite macroscopic devices through microcrystal orientation. Our experiments have shown that there is a strong anticorrelation between current and external bias in random-perovskite films at the microscopic level. However, the ordered-perovskite films exhibit significant improvements in current homogeneity and optoelectronic properties.…”
Section: Resultsmentioning
confidence: 78%
“…While the SPO PCEs for both types of devices were similar, the integrated J sc of ordered-perovskite devices was slightly higher, reinforcing the positive impact of crystal orientation (Figure i,j). Currently, there is a widespread discussion on improving the performance of perovskite macroscopic devices through microcrystal orientation. Our experiments have shown that there is a strong anticorrelation between current and external bias in random-perovskite films at the microscopic level. However, the ordered-perovskite films exhibit significant improvements in current homogeneity and optoelectronic properties.…”
Section: Resultsmentioning
confidence: 78%
“…To date, researchers have devoted considerable attention to the meticulous selection of additives that enhance the performance of PSCs. These additives encompass a variety of options, including commonly used ones such as organic and inorganic salts [13] , organic molecules [14] , ionic liquids (ILs) [15] , polymers [16] , and nanoparticles [17] . Among the various additives, ILs have received widespread attention.…”
Section: Introductionmentioning
confidence: 99%